The Moderating effect of Firm Size on the impact of Dynamic Capabilities on sustainable Performance of food manufacturing firms Kenya - Kitenga, Gabriel; J. M. Kilika,; A. W. Muchemi, (Technium Social Sciences Journal, 2020)
This study sought to investigate the effect of dynamic capabilities on the performance of selected manufacturing firms in Kenya. It also aimed at examining the moderating effect of firm size on the effect of dynamic capabilities on the performance of manufacturing firms. The study utilized both the descriptive and explanatory research design which was cross-sectional survey in nature. The study population comprised of all the 70 food manufacturing listed in the Kenya Association of Manufacturer’s directory. Self-administered questionnaires were used to collect primary data from 190 respondents. Multiple regression analysis was used to establish the nature and magnitude of the relationships between the independent and dependent variables. The findings indicate that there is a significant positive relationship between dynamic capabilities and performance of food manufacturing firms in Kenya. Firm size was found not to have significant relationship with firm and does not moderate the relationship between dynamic capabilities and performance. The findings supported the theoretical foundation of the dynamic capabilities theory that a firm performance and sustainable competitive advantage depends on its ability to reacting rapidly and flexibly to changing market environments. The study recommends that policy makers should link performance of food manufacturing firms with national goals and in this regard, include acquisition of dynamic capabilities by food manufacturing firms in their policy interventions aimed at increasing food security.